SELF-EDUCATION OF THE PERSONALITY IN THE PROCESS OF PROFESSIONAL TRAINING OF THE STUDENT (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The process of self-training providing not only mastering in the ways of acquisition of necessary knowledge, but also independence formation as professionally significant quality of the person is the basis of continuous self-education. Therefore formation of readiness of the future experts to self-training and display of creative activity becomes one of the major problems of the higher school today. The modern pedagogic represents development and self-development of the person as uniform, complete process. Training and self-training are dialectically interconnected: showing activity and making efforts, the person trains itself with the assistance of other people. Self-training is the realized creative activity on mastering by informative, communicative ways and other kinds of activity, to acquisition on this base of necessary knowledge, skills and abilities and formation of the qualities providing self-development of the person.